MATH SOLVE

2 months ago

Q:
# I need the answers thanks :)

Accepted Solution

A:

1.) y=3

2.) y=13

2y + y = 3y , 22+17= 39

3y = 39 , divide 3 on each side (which cancels out the 3 with the y which leaves you with y)

3.) y=10

3y - y = 2y , 35-15= 20

2y=20 , do the same as # 2.

4.) y=4

9y - 5y = 4y , 48-32= 16

4y=16, do the same as #2 & #3

5.) (4,5)

x + 3y = 19

2x - 3y = -7

solve for x first ; x + 2x= 3x , 19-7 = 12; 3x = 12 ; divide 3 ; x= 4. You know have to make the x's cancel out. so I will multiply -2 on the first equation. -2(x+3y=19)

-2x - 6y = -38

2x - 3y = -7

Now solve for y ; -6y + -3y = -9y , -38 + -7 = -45; -9y=-45 ; divide by -9 (since they are both negative your answer will be positive) ; y= 5

6.) (6,8)

x + 4y = 38

-x - 3y = -30

solve for y first ; 4y - 3y = y , 38-30 = 8; y=8 (that simple!) Now you need to find a common multiple for 4 & 3 which is 12. So you will have to multiply each equation by either 4 or 3.

(x + 4y = 38)*3 = 3x + 12y = 114

(-x - 3y = -30)*4 = -4x - 12y = -120

solve for x ; 3x - 4x = -x , 114-120= -6 ; -x=-6. Since the x has a negative that means there's still a 1 there so -1x=-6 ; you will need to divide this which makes the 6 a positive; x=6

2.) y=13

2y + y = 3y , 22+17= 39

3y = 39 , divide 3 on each side (which cancels out the 3 with the y which leaves you with y)

3.) y=10

3y - y = 2y , 35-15= 20

2y=20 , do the same as # 2.

4.) y=4

9y - 5y = 4y , 48-32= 16

4y=16, do the same as #2 & #3

5.) (4,5)

x + 3y = 19

2x - 3y = -7

solve for x first ; x + 2x= 3x , 19-7 = 12; 3x = 12 ; divide 3 ; x= 4. You know have to make the x's cancel out. so I will multiply -2 on the first equation. -2(x+3y=19)

-2x - 6y = -38

2x - 3y = -7

Now solve for y ; -6y + -3y = -9y , -38 + -7 = -45; -9y=-45 ; divide by -9 (since they are both negative your answer will be positive) ; y= 5

6.) (6,8)

x + 4y = 38

-x - 3y = -30

solve for y first ; 4y - 3y = y , 38-30 = 8; y=8 (that simple!) Now you need to find a common multiple for 4 & 3 which is 12. So you will have to multiply each equation by either 4 or 3.

(x + 4y = 38)*3 = 3x + 12y = 114

(-x - 3y = -30)*4 = -4x - 12y = -120

solve for x ; 3x - 4x = -x , 114-120= -6 ; -x=-6. Since the x has a negative that means there's still a 1 there so -1x=-6 ; you will need to divide this which makes the 6 a positive; x=6